Public order policing in the UK - Clark, Claire (Public Order Policing, 2024)
This article highlights the principles of public order policing in the United Kingdom, followed by an overview on relevant legislation and guidelines. Then, the chapter explains the system of public order public safety policing, focusing on the tasks of the overall strategic commander referred to as Gold. After describing some important components of public order policing, the author shows how all those aspects and potential strategies can be operationalised by using several examples and case studies.